Marriage patterns and some issues related to adolescent marriage in Bangladesh - M. Mazharul Islam; Mamun Mahmud (Asia-Pacific Population Journal, 1996)
Adolescents, their parents and the community should be made more aware of the negative consequences of early marriage, early pregnancy and large family size